EUROPEIZACJA PRAWA KARNEGO GOSPODARCZEGO (NA PRZYKŁADZIE NIEMIECKIEJ USTAWY O ZWALCZANIU NIEUCZCIWEJ KONKURENCJI) - Nestoruk, Igor B. (Wydział Prawa i Administracji UAM, 2003)
The article explores the issue of the remarkable influence of the community-based law on the criminal law of the member states of the EU. There is a significant number of examples illustrating this phenomenon especially in the area of the criminal law against white collar crimes. The consequences of this pending process are deliberately analyzed on the example of criminal acts against unfair market practices. The author has chosen the criminal provisions valid under the German Act against Unfair Competition of 1909 (especially its penal sanctions against misleading advertisement) in order to show the significance of the process of „europeanization” of economic criminal law.
EUROPEANIZATION OF ECONOMIC CRIMINAL LAW - ON EXAMPLE OF GERMAN ACT AGAINST UNFAIR COMPETITION